HeSARIC: A Heterogeneous Cyber–Physical Robotic Swarm Framework for Structural Health Monitoring with Augmented Reality Representation - Alireza Fath; Christoph Sauter; Yi Liu; Brandon Gamble; Dylan Burns; Evan Trombley; Sai Krishna Reddy Sathi; Tian Xia; Dryver Huston (Micromachines)
This study proposes a cyber–physical framework for the integration of a heterogeneous swarm of robots, sensors, microrobots, and AR for structural health monitoring and confined space inspection based on the application’s unique challenges. The structural issues investigated are cracks in the walls, deformation of the structures, and damage to the culverts and devices commonly used in buildings. The PC and augmented reality interfaces are incorporated for human–robot collaboration to provide the necessary information to the human user while teleoperating the robots. The proposed interfaces use edge computing and machine learning to enhance operator interactions and to improve damage detection in confined spaces and challenging environments. The proposed swarm inspection framework is called HeSARIC.